Madrasah pada Masa Keemasan Islam: Studi Perbandingan dengan Madrasah Saat Ini - Mahyudin, Edy; Rusli, Risan; Sukardi, Ismail; Hasan, Muflikhul (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the characteristics of madrasas during the Golden Age of Islam and compare them with the condition of contemporary madrasas. The research method used is library research with a descriptive qualitative approach. Data were obtained from books on the history of Islamic education, scientific journal articles, research reports, and official documents on modern madrasas. Content analysis was employed to examine the characteristics of classical madrasas, while comparative analysis was used to compare them with present-day madrasas. The results show that madrasas in the Islamic Golden Age flourished due to the integration of religious and rational sciences, strong support through waqf, the presence of scholar-scientists as educators, and an academic culture open to dialogue and research. Meanwhile, modern madrasas have experienced significant progress in curriculum development and scientific integration, but still face challenges such as limited facilities, teacher competency gaps, and learning methods that are not yet fully innovative. The discussion emphasizes the importance of revitalizing the values of classical madrasas through strengthening research, integrating knowledge, and modernizing pedagogy so that madrasas can compete globally without losing their Islamic identity